2007
DOI: 10.1016/j.cub.2007.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Intimacy Affects Structure and Coevolutionary Dynamics in Mutualistic Networks

Abstract: The structure of mutualistic networks provides clues to processes shaping biodiversity [1-10]. Among them, interaction intimacy, the degree of biological association between partners, leads to differences in specialization patterns [4, 11] and might affect network organization [12]. Here, we investigated potential consequences of interaction intimacy for the structure and coevolution of mutualistic networks. From observed processes of selection on mutualistic interactions, it is expected that symbiotic interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
247
1
28

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(290 citation statements)
references
References 30 publications
14
247
1
28
Order By: Relevance
“…In addition to simulations of mutualistic communities starting with random interactions networks and then "reorganizing" toward a more optimal state, we also implement a more realistic scenario in which mutualistic communities progressively assemble and are optimized over the course of evolutionary timescales 23,24 . Indeed, we find that the final result is the same, i.e., the final optimized networks display a nested architecture (Supplementary Information).…”
mentioning
confidence: 99%
“…In addition to simulations of mutualistic communities starting with random interactions networks and then "reorganizing" toward a more optimal state, we also implement a more realistic scenario in which mutualistic communities progressively assemble and are optimized over the course of evolutionary timescales 23,24 . Indeed, we find that the final result is the same, i.e., the final optimized networks display a nested architecture (Supplementary Information).…”
mentioning
confidence: 99%
“…Modular food-webs are defined by dietary resource segregation among consumers [67]. Resource segregation can occur over ecological, but also evolutionary timescales, where coevolutionary relationships may begin to constrain the plasticity of trophic interactions, promoting compartmentalization [65]. In isolated environments, where neighboring systems are similar and invasions are rare, di↵erentiation of resources and the subsequent development of modular interactions may be more likely to occur and be reinforced over time.…”
Section: Linking Species Interactions To Large-scale Community Structurementioning
confidence: 99%
“…(leguminosae -caesalpinioideae) were found in continuous forest, hosting different ant species (Petini-Benelli and izzo 2011) but never M. epicharis. indeed, Bruna et al (2005) reported that M. madida is extremely rare in areas of continuous forest in central Amazon and several authors have found M. madida in areas near to rivers (Mcvaugh 1956; The symbiotic relationship between ants and myrmecophytes is suggested be specialized and compartmentalized (Guimarães et al 2007). in this type of relationship both parts have different adaptations to select their association (mutualism filters) (Davidson et al 1989;Ferdele 1997;Dáttilo et al 2009b).…”
mentioning
confidence: 99%
“…We did not observe ant alates and coccoid symbionts living in the domatias. The symbiotic relationship between ants and myrmecophytes is suggested be specialized and compartmentalized (Guimarães et al 2007). in this type of relationship both parts have different adaptations to select their association (mutualism filters) (Davidson et al 1989;Ferdele 1997;Dáttilo et al 2009b).…”
mentioning
confidence: 99%
See 1 more Smart Citation